2011
DOI: 10.1175/2011jamc2664.1
|View full text |Cite
|
Sign up to set email alerts
|

A Spatiotemporal Analysis of Historical Droughts in Korea

Abstract: The climatological characteristics of drought in South Korea were investigated using daily precipitation data for 1777-2008. The effective drought index was used to quantify the drought intensity. As a result, five characteristics were discovered. First, South Korea can be divided into four drought subregions (the central, southern, and east coastal regions and Jeju Island) using hierarchical cluster analysis. Second, a map for longterm drought conditions in the four subregions is created that allows identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 36 publications
0
40
0
4
Order By: Relevance
“…Based on the predicted values of the EDI, the severity and the duration of drought at the four sites were deduced following the approach of Kim et al (2011) where a drought month was identified when the monthly value of the EDI was negative (i.e. rainfall conditions were lower rainfall than the normal period).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the predicted values of the EDI, the severity and the duration of drought at the four sites were deduced following the approach of Kim et al (2011) where a drought month was identified when the monthly value of the EDI was negative (i.e. rainfall conditions were lower rainfall than the normal period).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Dogan et al (2012) found the EDI to be very sensitive to subtle changes in rainfall, and showed the superiority of the EDI for continuous monitoring of short and long-term drought. The study of Byun et al (2008) also showed the ability of the EDI for prediction of future drought in Korea using periodicity analysis of long-term observed dataset and the study of Kim et al (2011) developed a spatio-temporal map using wavelet transformations for the Korean region. Despite a plethora of studies using the EDI for drought assessment in East Asia, to our best knowledge, no study on the prediction of the EDI has been conducted in Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate minor droughts, all drought events with a duration less than 15 days were excluded from the analysis (values up to 5 days are used by Hisdal et al, 2004;Birkel, 2005;Fleig et al, 2006;Van Loon et al, 2011a, but various studies showed that minor droughts can have durations up to 20 days; Hisdal, 2002;Fleig et al, 2005;Kaznowska and Banasik, 2011;Kim et al, 2011). Of the remaining drought events, a few were found to be not real drought events, but rather artefacts of the method used.…”
Section: Threshold Level Methodsmentioning
confidence: 99%
“…The EDI is a daily index that represents a continuous period and daily strength changes as objective values; it is an intensive measure that considers water accumulation with the weighting function of time passage. The merits of the EDI have been verified by many studies (Morid et al 2006;Pandey et al 2008;Lee and Byun 2009;Kim et al 2011;Lee et al 2012). The EDI is calculated using three equations:…”
Section: Introductionmentioning
confidence: 76%